Factor structure of psychophysical training of cadets of senior school age to the military professional activity. - Mikhuta I.Ju (Kharkov National Pedagogical University, 2011)
The paper identified factor structure of the psychophysical preparedness of Suvorov military school. It is presented a structural and functional hierarchy of the leading and background components of psychomotor, and focal conditioned qualities, which allows to develop a program of psychophysical training troops aimed at improving the psychomotor, conditioned and coordination abilities to enhance professional-applied physical training and psycho-physical readiness to meet the challenges of the future military career.